Solar cell materials : developing technologies - Conibeer, Gavin; Willoughby, Arthur (Chichester, West Sussex : John Wiley & Sons Ltd, 2014)
'This book presents a comparison of solar cell materials, including both new materials based on organics, nanostructures and novel inorganics and developments in more traditional photovoltaic materials. Introductory chapters cover physical characterisation and fundamental physical limits including the importance of characterization in assessing semiconductor and PV properties with particular emphasis on new techniques or new applications. Later chapters discuss developments in current technologies such as bulk crystalline solid-state semiconductor materials, and emerging materials and approaches such as amorphous and microcrystalline silicon solar cells. Finally, the book surveys the materials and materials trends in the field including third generation solar cells (multiple energy level cells, thermal approaches and the modification of the solar spectrum) with an eye firmly on low costs, energy efficiency and the use of abundant non-toxic materials'--
Includes bibliographical references and index.
Keywords: Solar cells -- Materials; Photovoltaic cells -- Materials